2020
DOI: 10.3390/en13112814
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermophilic Treatment of Grass and Leaves to Produce Hydrogen, Methane and VFA-Rich Digestate: Preliminary Results

Abstract: In this study, the feasibility of hydrogen and methane production from grass and leaves via hyperthermophilic anaerobic digestion was investigated. The hyperthermophilic treatment of grass at 70 °C resulted in the highest concentrations of volatile fatty acids (TVFA) and reducing sugars in the supernatant of over 21 and 6.5 g/L reported on day 3 and 4 of the experiment. In contrast, hydrolysis and acidification of leaves performed slower and with lower efficiency, as the peak concentrations of TVFA and reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In previous studies, the hyperthermophilic preliminary treatment was found to considerably increase the methane and hydrogen yield from grass and leaves in the subsequent mesophilic and thermophilic step and overall process performance. On the other hand, the single-stage anaerobic mesophilic or thermophilic treatment of these materials is characterized by low efficiency due to the specific structure of grass and leaves, which are mainly composed of recalcitrant lignocellulosic compounds [18]. As mentioned above, the hyperthermophilic pretreatment was only applied to grass and leaves as they were much more resistant to biological treatment than kitchen waste.…”
Section: Hyperthermophilic Treatment Of Grass and Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the hyperthermophilic preliminary treatment was found to considerably increase the methane and hydrogen yield from grass and leaves in the subsequent mesophilic and thermophilic step and overall process performance. On the other hand, the single-stage anaerobic mesophilic or thermophilic treatment of these materials is characterized by low efficiency due to the specific structure of grass and leaves, which are mainly composed of recalcitrant lignocellulosic compounds [18]. As mentioned above, the hyperthermophilic pretreatment was only applied to grass and leaves as they were much more resistant to biological treatment than kitchen waste.…”
Section: Hyperthermophilic Treatment Of Grass and Leavesmentioning
confidence: 99%
“…Before closure, the top of each tank was flushed with nitrogen gas to provide anaerobic conditions. Considering the earlier experiences, the hyperthermophilic pretreatment time was set for 3 days [18]. After completion of the process, the digested materials were analyzed for pH, soluble COD, ammonium nitrogen, and volatile fatty acids.…”
Section: Hyperthermophilic Pretreatment Of Grass and Leavesmentioning
confidence: 99%
“…The AD process with the addition of isolated bacteria was carried out in a similar manner to the process carried out in previous studies [ 23 ]. The AD was carried out in two variants: I—grass pretreated at 70 °C, mixed with water in the ratio 1:2, with the addition of bacteria (PGB); and II—raw grass mixed with water in the ratio 1:2, with the addition of bacteria (GB).…”
Section: Methodsmentioning
confidence: 99%